Determination of Custody Rights of Minor Children to Father Post-Divorce in Review of Islamic Law (Maṣlaḥah Mursalah) - Anis Mahmudah, Siti; Umam, Fadoilul (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2024)
The separation of parents often results in neglect of child care. This can be seen in societies where divorce often occurs. In conditions like this, problems arise as to which parent has more right to care for the child. The settlement can be carried out through a legal process with a court decision with the aim of ensuring legal certainty in the future. This research aims to find out the basic considerations of judges at the Surakarta Religious Court in determining custody of minor children to their fathers and how the legal review of legal considerations in this case is carried out. This type of research is library research which takes secondary data sources in the form of decisions of the Surakarta Religious Court. This research uses data analysts who discuss and explain the judge's considerations in determining custody of minor children in terms of Maṣlaḥah law. The results of the research show that the judge's consideration in determining custody of a minor child to his father is based on law number 23 of 2002 article 13 concerning child protection after divorce, and law number 1 of 1974 concerning marriage as well as a compilation of Islamic law articles 105 and 156 which regulates the rights of children who are not yet mumayiz, And secondly, the judge's consideration in determining custody of a minor child to the father is based on the maṣlaḥah theory, namely adhering to the five pillars of maqāṣid asy-syari’ah including the maintenance of the child's mind, religion, soul, property, all of which aims to realize justice and benefit for the child. in accordance with the objectives of the problem.